Efektivitas Metode As-Sam’iyah As-Syafawiyah dalam Meningkatkan Pembelajaran Bahasa Arab Siswa Kelas VI MIS Islamiyah - Limah Nurlatipah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This research is a classroom action research aimed at determining whether the use of the As-Sam'iyah Asy-Syafawiyyah method is effective in improving learning at MIS Islamiyyah Taringgul Tonggoh. The As-Sam'iyah Asy-Syafawiyyah method emphasizes an active listening and speaking approach, enabling students to more easily understand and use Arabic in communication. It can also enhance Arabic language learning for sixth-grade students at MIS Islamiyyah Taringgul Tonggoh. To obtain the research results, the researcher conducted a qualitative approach. The population used in this study consisted of 20 sixth-grade students at MIS Islamiyyah. To improve Arabic learning, the researcher conducted the study in two cycles using the Kurt Lewin model. Each cycle consists of four components: planning, action, observation, and reflection. The data collection techniques used were interviews, observations, and tests. The data obtained were analyzed descriptively and using the percentage of learning completeness. The conclusion is that the As-Sam'iyah Asy-Syafawiyyah method is proven to be effective in improving Arabic language learning for sixth-grade students at MIS Islamiyyah Taringgul Tonggoh.